Undomesticated dissent: democracy and the public virtue of religious nonconformity - Freeman, Curtis W. (Baylor University Press, 2017)
"This book seeks to tell the story of religious dissent as a polemical and dialectical argument from the seventeenth century to the present, from Bunhill Fields to Plymouth Rock. Its narrative displays the ongoing contestation about the proper mode of dissent from evangelical to political to radical, and more importantly it places Bunyan, Defoe, and Blake and their writings within this extended argument"--Preface